FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GASTRITIS PADA PASIEN YANG BEROBAT DI PUSKESMAS - Muhammad Safii; Dina Andriani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Gastritis is a health problem that is still very common in the community. gastritis is an inflammation or bleeding in the gastric mucosa caused by irritation, infection, and irregularities in eating patterns. Based on observations at the Lak-Lak Public Health Center in Ketambe Sub-District, Southeast Aceh Regency, the number of gastritis sufferers in January to March 2019 totaled 128 people and to date the factors associated with the incidence of gastritis in this region are not yet clearly known. This study aims to determine the factors associated with gastritis in patients seeking treatment at the Lak-Lak Public Health Center in Ketambe District, Southeast Aceh Regency in 2019. This study used a cross sectional approach. The results of the study using the Chi-square test based on factors of eating habits and coffee drinking habits are factors associated with gastritis because of the p-value of ≤ 0.05. While smoking habits, alcohol consumption habits and stress are factors that are not related to gastritis due to the p-value ≥ 0.05. Keywords : Gastritis, Eating Habits, Coffee Drinking habits, Smoking Habits, Alcohol Consumption Habits and Stress.